Gambaran Strategi Koping dan Tingkat Stres pada Ibu Postpartum - Wulandari, Ida Ayu Putri; Kusuma, Made Dian Shanti; Sari, Wulan Tertiana (Jurnal Kesehatan, 2023)
The postpartum period is a transitional period experienced by a mother after giving birth. At the period, postpartum mothers are prone to experience stress. Coping mechanisms are abilities or methods used by a person in dealing with stressors or sources of stress that arise, where this is related to the type of coping strategy used. The purpose of this study was to describe the types of coping strategies and stress levels in postpartum mothers. This research used a cross-sectional approach. The sampling technique used in this research is non-probability sampling with purposive sampling. The number of samples used were 120 postpartum mothers. The questionnaire used consisted of two questionnaires, namely: Ways of Coping Scale (WOC) and Depression Anxiety Stress Scale (DASS). The results showed that the most frequently used coping strategy was the Accepting Responsibility type as the highest percentage among the others, which was 68.3%. Meanwhile, the level of stress experienced by postpartum mothers in this study was in the normal, mild and moderate range, with the most experienced was mild stress with a percentage of 46.7%. The coping strategies used are very diverse, where both coping strategies that focus on tasks as well as emotions are used; and also the stress levels depicted are in the normal, low, and moderate ranges.